Job Demands, Perceived Organizational Support, and Employee Performance: Employee Engagement as a Mediator - Ririn Widiawati Ananta; Dedi Muhammad Siddiq; Eteh Resa Asyifa; Tonny Odokonyero (Cakrawala Repositori IMWI)
This inquiry aims to evaluate the effect of Job Demands and Perceived Organizational Support (POS) on Employee Performance, with Employee Engagement serving as a mediating variable in the industrial manufacturing field. The research applies a quantitative associative approach using Structural Equation Modeling with Partial Least Squares (SEM PLS). The target population consisted of 199 employees, whereas 133 respondents were determined using the Slovin formula at a 5% margin of error. Data were gathered using a structured questionnaire based on a five point Likert scale. The outcomes indicate that Perceived Organizational Support strengthens Employee Engagement and Employee Performance, while Job Demands diminish Employee Engagement together with Employee Performance. Furthermore, Employee Engagement demonstrates a significant favorable effect on Employee Performance. The mediating analysis verifies that Employee Engagement serves as an important connecting mechanism between Job Demands and Employee Performance, as well as between Perceived Organizational Support and Employee Performance. Addressing the limited empirical evidence in labor intensive and seasonal manufacturing contexts, this study extends the Job Demands Resources (JD R) framework by validating Employee Engagement as a key mediating channel and provides managerial guidance for balancing Job Demands and strengthening institutional support to enhance workforce productivity. The findings strengthen the Job Demands Resources (JD R) framework and emphasize the importance of harmonizing Job Demands with adequate organizational support to enhance Employee Engagement and performance achievements. The research further offers applicable recommendations for leaders in formulating human resource strategies intended to foster Employee Engagement and elevate organizational efficiency within manufacturing industries